Hubungan Paparan Asap Pembakaran Gerabah Dengan Kejadian ISPA Pada Balita - Wasliah, Indah; Romadonika, Fitri; Pratiwi, Eka Adithia; Putri, Anggi Hapsari (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2022)
Acute Respiratory Infections (ARI) always rank first in the cause of death in the infant and toddler group in Indonesia. Air pollution by combustion fumes is one of the factors causing ARI in toddlers. Exposure to pottery burning smoke is one of the air pollution in Banyumulek village. An epidemiological study showed long-term smoke exposure showed an increase in bronchitis symptoms in children and was also associated with decreased lung function. The purpose of this study was to determine the relationship between exposure to pottery burning smoke and the incidence of ARI in toddlers in the Banyumulek Health Center Working Area, West Lombok. This study is an analytical survey study with a cross-sectional approach, purposive sampling techniques, respondents totaling 75 respondents. The measuring instruments used were questionnaires about exposure to pottery combustion smoke and ARI event questionnaires. This research was conducted in the Banyumulek Health Center Working Area of West Lombok and this research was conducted on May 25-June 6 year. The statistical test used in this study is Chi-Square. Results: The results of this study showed a significant relationship between exposure to pottery burning smoke and the incidence of ARI in toddlers in Banyumulek Village with a P-Value of 0.014<0.05. Exposure to pottery burning smoke is one of the causes of ARI in toddlers in Banyumulek Village. It is hoped that parents will pay more attention to the health of toddlers and increase knowledge about the dangers of exposure to pottery burning smoke for the health of their toddlers.